2017
DOI: 10.1111/den.12878
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of digital single‐operator cholangioscope for diagnostic and therapeutic procedures (with videos)

Abstract: Although additional cases and a randomized, controlled study with another cholangioscope are needed, diagnostic and therapeutic procedures using SPY-DS appear to be feasible and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 29 publications
4
92
0
Order By: Relevance
“…9,21 In summary, recent studies and our results support an improved imaging quality of digital SOCs that might increase the efficacy of optically diagnosing malignancy; however validated optical criteria for malignancy detection are missing. 6,9,10 The second main indication for cholangioscopy was complex biliary stone disease. In our study, the digital SOC-guided EHL allowed complete biliary stone clearance in all patients (9/9).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…9,21 In summary, recent studies and our results support an improved imaging quality of digital SOCs that might increase the efficacy of optically diagnosing malignancy; however validated optical criteria for malignancy detection are missing. 6,9,10 The second main indication for cholangioscopy was complex biliary stone disease. In our study, the digital SOC-guided EHL allowed complete biliary stone clearance in all patients (9/9).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with other digital SOC studies that report stone removal rates of 86-100%. 7,9,10 According to a meta-analysis including 244 cholangioscopies in patients with difficult stone disease, the success rate for fibre-optic SOC was 87%. 22 We conclude that compared with fibre-optic SOC, for complex stone disease, the improved digital imaging quality might not improve biliary stone clearance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ERC‐guided pathological examinations for biliary stricture seem to have insufficient accuracy unless a lesion projects into a lumen of the bile duct . A resent prospective study reported that digital cholangioscopy had high accuracy for the diagnosis of biliary disease . However, preoperative pathological diagnosis of CD carcinoma was not made in any of the cases reported.…”
Section: Brief Explanationmentioning
confidence: 99%